Alignment in total knee arthroplasty: what's in a name?. (March 2020) - Oussedik, Sam; Abdel, Matthew P.; Victor, Jan; Pagnano, Mark W.; Haddad, Fares S.
Abstract : Dissatisfaction following total knee arthroplasty is a well-documented phenomenon. Although many factors have been implicated, including modifiable and nonmodifiable patient factors, emphasis over the past decade has been on implant alignment and stability as both a cause of, and a solution to, this problem. Several alignment targets have evolved with a proliferation of techniques following the introduction of computer and robotic-assisted surgery. Mechanical alignment targets may achieve mechanically-sound alignment while ignoring the soft tissue envelope; kinematic alignment respects the soft tissue envelope while ignoring the mechanical environment. Functional alignment is proposed as a hybrid technique to allow mechanically-sound, soft tissue-friendly alignment targets to be identified and achieved. Cite this article: Bone Joint J 2020;102-B(3):276–279.